Promoting adults’ knowledge for engaging young children with numerical activities. - Levenson, Esther; Barkai, Ruthi; Tsamir, Pessia; Tirosh, Dina (Scientia in educatione, 2022)
Considering that young children spend a great deal of time outside of school, there is a need to increase the expertise of adults when it comes to engaging young children with numerical activities. This study presents the Cognitive Affective Mathematics Adult Education framework used to design such a course for interested adults. Focusing on promoting young children’s competency for comparing sets, we illustrate how the framework was used to design the course and how the framework was used to analyze the impact of the course on the relevant expertise of the participating adults. The findings indicated that the adults had gained knowledge in the various strategies one can use to compare sets, had become aware of the importance of evaluating those strategies, and had acquired the ability to take the children’s ages and abilities into account when tailoring activities that engage them with set comparisons.